Association between COVID-19 vaccination and critical outcomes among older adults with dementia: a comparative cohort study - Zorian Radomyslsky; Sara Kivity; Shira Lidar; Netta Bentur; Liat Korn; Rachel Nissanholtz-Gannot; Rachel Nissanholtz-Gannot; Shelley Sternberg; Inbal Halevi Hochwald; Orna Reges; Yaniv Alon; Mor Saban (Frontiers Media S.A., 2023)
BackgroundAs COVID-19 vaccines became available, understanding their potential benefits in vulnerable populations has gained significance. This study explored the advantages of COVID-19 vaccination in individuals with cognitive disorders by analyzing health-related variables and outcomes.MethodsA prospective cohort study analyzed electronic medical records of 25,733 older adults with cognitive disorders and 65,544 older adults without cognitive disorders from March 2020 to February 2022. COVID-19 vaccination status was the primary exposure variable, categorized as fully vaccinated or unvaccinated. The primary outcomes measured were all-cause mortality and hospitalization rates within 14 and 400 days post-vaccination. Data on vaccination status, demographics, comorbidities, testing history, and clinical outcomes were collected from electronic health records. The study was ethically approved by the relevant medical facility's Institutional Review Board (0075-22-MHS).ResultsVaccinated individuals had significantly lower mortality rates in both groups. In the research group, the mortality rate was 52% (n = 1852) for unvaccinated individuals and 7% (n = 1,241) for vaccinated individuals (p < 0.001). Similarly, in the control group, the mortality rate was 13.58% (n = 1,508) for unvaccinated individuals and 1.85% (n = 936) for vaccinated individuals (p < 0.001), despite higher COVID-19 positivity rates. In the research group, 30.26% (n = 1,072) of unvaccinated individuals tested positive for COVID-19, compared to 37.16% (n = 6,492) of vaccinated individuals (p < 0.001). In the control group, 17.31% (n = 1922) of unvaccinated individuals were COVID-19 positive, while 37.25% (n = 18,873) of vaccinated individuals tested positive (p < 0.001). Vaccination also showed potential benefits in mental health support. The usage of antipsychotic drugs was lower in vaccinated individuals (28.43%, n = 4,967) compared to unvaccinated individuals (37.48%, n = 1,328; 95% CI [0.92-1.28], p < 0.001). Moreover, vaccinated individuals had lower antipsychotic drug prescription rates (23.88%, n = 4,171) compared to unvaccinated individuals (27.83%, n = 968; 95% CI [−1.02 to −0.63], p < 0.001). Vaccination appeared to have a positive impact on managing conditions like diabetes, with 38.63% (n = 6,748) of vaccinated individuals having diabetes compared to 41.55% (n = 1,472) of unvaccinated individuals (95% CI [0.24, 0.48], p < 0.001).DiscussionThe findings highlight the importance of vaccination in safeguarding vulnerable populations during the pandemic and call for further research to optimize healthcare strategies for individuals with cognitive disorders.